Recognition Of Investment Properties: The Case Of Turkey - Sabuncu, Birsel (European Scientific Journal, ESJ, 2016)
Investment properties have come into our literature by the inurement of TAS. Investment properties are the properties that business aims to keep long in its hands because of their profit from increase in long-term value and rental income. The recognition of investment properties, which is under TAS 40, is not included yet in Uniform Chart of Accounts practise. Although it is not in vurrent account plan, investment properties are in the reporting as a seperate item before tangible assets in "Financial Statements and User Guide Samplesâ€ in line with Turkey Account Standards. The purpose of the study is to contribute to the literature by recognising with the reference of "Financial Statement Examples and Usage Guide" published by Accounting and Auditing Standards Authority, and providing information about the invesment properties, which are in practise newly, in the framework of TAS 40. It will be easier to adapt the reforms of the Accounting Standards of Turkey and the application unity of users will be achived along with making a number of changes in Uniform Chart of Accounts in the recognition of investment properties which are one of the reforms of Accounting Standards of Turkey.